Maisy goes to the city - Cousins, Lucy. (Somerville, Mass. : Candlewick Press, 2011)
Maisy and Charley visit their friend Dotty, who lives in a big city filled with noisy traffic, enormous buildings, and crowded sidewalks.
Publisher's Weekly
Publisher's Weekly, March 2011
1.6
K-3.
K-3
Keywords: City and town life -- Fiction; Maisy (Fictitious character : Cousins) -- Juvenile fiction; Mice -- Juvenile fiction; City and town life -- Fiction; Maisy (Fictitious character : Cousins) -- Fiction; Mice -- Fiction; City and town life -- Fiction; Maisy (Fictional character : Cousins) -- Fiction; Mice -- Fiction; Picture books for children